Tiny Tales: A Feast for Friends - Waldo, Steph ([Place of publication not identified] : Harperalley, 2022)
I Can Read Comics is a new early reader line that familiarizes children with the world of graphic novel storytelling and encourages visual literacy in emerging readers.
Keywords: Graphic novels; Cartoons and comics; Reading (Early childhood) -- United States